STUDI VEGETASI HUTAN RAWA AIR TAWAR DI CAGAR ALAM RIMBO PANTI, SUMATERA BARAT - Razali Yusuf; Purwaningsih Purwaningsih (Research Center for Biology-Indonesian Institute of Sciences, 2009)
A Vegetation study of some different freshwater swamp forests in Rimbo Panti Nature Reserve, West Sumatera was carried out with a quadrat methode.The results of a floristic inventory of trees with DBH e